Proporsi Larva Aedes aegypti dan Aedes albopictus, Hubungannya dengan Kejadian Demam Berdarah Dengue di Daerah Endemik Suburban Kabupaten Sleman, Yogyakarta - Bobby Fahmi Muldan Pahlevi; Tri Wulandari Kesetyaningsih (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Dengue Hemorrhagic Fever (DHF) is transmitted by Aedes aegypti and Ae. albopictus. Aedes aegypti chooses to live indoors and Ae. albopictus in outdoors. Aedes aegypti has been proven to play a role in dengue transmission in urban areas. It is assumed that suburbs dominated by gardens, so it is possible that Ae. albopictus acts as a vector. The study aimed to analyze the relationship between Ae. albopictus and DHF incidence in suburban area. The study was conducted in Godean, Sleman Regency. 280 ovitrap were placed indoors and outdoors at across seven villages. Each village was represented by one hamlet, so there were 40 ovitrap of each hamlet. The proportion of ovitrap containing Ae. aegypti and Ae. albopictus larvae was calculated. The results showed that Ae. aegypti larvae was more indoors (78.50%) than outdoors (21.45%) in all villages and negatively correlates with DHF (p=0.036; r=-0.776). Aedes albopictus larvae is more commonly found in gardens (80.64%) than in homes (19.36%) and does not correlate with DHF (p = 0.702). It was concluded that in suburban endemic area of ​​Sleman Regency, Ae. aegypti larvae was more indoors and negatively correlated with DHF. Aedes albopictus larva was more in the garden and did not correlate with DHF incidence.